Estrutura e estado de explotação dos estoques do Jurupoca, Hemisorubim platyrhynchos, e do Jurupensém, Sorubim cf. lima, na Bacia do Rio Cuiabá, Pantanla Mato-Grossense - Penha, Jerry Magno Ferreira (2003)
The fishery is an important economic activity at Pantanal. This study describe and analyse the age, the individual growth, the structure, the exploitation and the management alternatives for the two pimelodidae catfish stocks fished in region. The Porthole Shovelnose Catfish, Ilemisorubim platyrhynchos , and the Duckbill Catfish, Sorubim lima, are, respectively, the sixth and the seventh bigger Pantanal pimelodidae catfish. The fishes were caught by comercial and experimental fisheries with hook and line in Cuiabá river, Pantanal. The age and the individual growth were studied from the (a partir dos) pectoral fin-spines. The estimates fo growth parameters were used to obtain estimate of instantaneous mortality rates for the stocks. The consequences of different managemtn actions for the fishes and the fisheries were assessed with (através) the Beverton and Holt relative yield per recruit model. The results indicate that Il. platyrhynchos and S. lima show slow growth and intermediate natural mortality coeficient. The longevity of Il. platyrhynchos is of 11,4 years, and of S. lima is of 9,6 years. The fisheries catches several fishes cohorts and, in general, individuals abovemean lenght of first maturation. Because historical data are not available it is hard to assess the effects of arising (crescente) fisheries pressure on the stocks. Nevertheless, the results of relative yield per recruit model simulations indicate that presente fisheries effort is below of a conservative biological reference point - the P 0,1. So, the two species stocks are underexploited . However, an arising of presente fisheries effort must be seen with caution because (uma vez que) the raltion between stocks size and recruitment for the two species is not knew